Corynosoma bullosum Linstow 1892 - Hernández-Orts, Jesús S.; Viola, M. Natalia Paso; García, Néstor A.; Crespo, Enrique A.; González, Raúl; García-Varela, Martín; Kuchta, Roman (Zenodo, 2015)
Corynosoma bullosum (Linstow, 1892) Host: Physeter macrocephalus Linnaeus Site in host: intestine Locality: Puerto Madryn (43º14'S, 65º02'W), Chubut province Specimens in collections: MML (accession numbers not provided)V References: Crespo et al . (1994, reported as Bolbosoma sp.) and Berón-Vera et al . (2008) Notes: Berón-Vera et al . (2008) re-examined the acanthocephalans collected by Crespo et al . (1994) and identified them as C. bullosum and Corynosoma sp. Published as part of Hernández-Orts, Jesús S., Viola, M. Natalia Paso, García, Néstor A., Crespo, Enrique A., González, Raúl, García-Varela, Martín & Kuchta, Roman, 2015, A checklist of the helminth parasites of marine mammals from Argentina, pp. 301-334 in Zootaxa 3936 (3) on page 305, DOI:10.11646/zootaxa.3936.3.1, http://zenodo.org/record/236696